2020
DOI: 10.1016/j.rbmo.2020.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Defining recurrent pregnancy loss: associated factors and prognosis in couples with two versus three or more pregnancy losses

Abstract: Center (LUMC) in the Netherlands, with recurrent pregnancy loss as his focus area. He obtained his Doctor of Medicine degree in 2020. As a medical student he has performed studies on his focus area of recurrent pregnancy loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Further, it should not be forgotten that couples with RPL have a high rate of healthy pregnancies. Youssef et al [38] found no cause in 71.5 % of women with RPL experience in their study. Although the chance of having a healthy pregnancy decreases with the increasing number of pregnancy losses, they found this possibility as 75 % even in those who had ≥ 4 pregnancy loss.…”
Section: Discussionmentioning
confidence: 62%
“…Further, it should not be forgotten that couples with RPL have a high rate of healthy pregnancies. Youssef et al [38] found no cause in 71.5 % of women with RPL experience in their study. Although the chance of having a healthy pregnancy decreases with the increasing number of pregnancy losses, they found this possibility as 75 % even in those who had ≥ 4 pregnancy loss.…”
Section: Discussionmentioning
confidence: 62%
“…We retrospectively searched patient's files referred to our thrombophilia unit from 2003 to 2018. Inclusion criteria were (1) women referred to our unit after at least one prior event of RF (early or late PL), (2) screened for thrombophilia, and (3) followed during their next pregnancy in our thrombophilia unit. We identified 175 women fitting our inclusion criteria.…”
Section: Study Populationmentioning
confidence: 99%
“…Reproductive failure (RF), defined as failure to carry pregnancy in term, is a frustrating event for childbearing aged women [1]. In most cases, etiological factors cannot be detected, and women are referred to hematology units for thrombophilia screen [2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive diagnostic workup offered to couples with RPL, underlying risk factors can be identified in only 25%–40% of couples 7 8. Limited understanding of mechanisms underlying RPL has the consequence that effective treatment options are often lacking.…”
Section: Introductionmentioning
confidence: 99%